2016
DOI: 10.1111/jam.13058
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus molecular detection in Uruguayan sewage samples reveals a high genetic diversity and GII.4 variant replacement along time

Abstract: This approach can be used as an indicator of the presence of a new GII.4 variant which can originate an increase in acute gastroenteritis outbreaks worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The screening of sewage water for human viruses began with the detection and monitoring of polioviruses (Sinclair et al 2008;, and since then it has been successfully extended to study the circulation of different enteric and nonenteric viruses in the human population (La Rosa et al 2010Cantalupo et al 2011;Di Bonito et al 2014;Smith et al 2015;Victoria et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The screening of sewage water for human viruses began with the detection and monitoring of polioviruses (Sinclair et al 2008;, and since then it has been successfully extended to study the circulation of different enteric and nonenteric viruses in the human population (La Rosa et al 2010Cantalupo et al 2011;Di Bonito et al 2014;Smith et al 2015;Victoria et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of studies describing in depth the impact of NoV and HAdV in the health of Uruguayan children, all the above-mentioned viruses have been reported as acute gastroenteritis causing agents in Uruguayan paediatric population, with incidences according the expected for RVA (37%) and HAstV (10%). Moreover, a wide dispersion as well as a wide genetic diversity in the Uruguayan environment has been recently reported for these viral pathogens (Victoria et al 2014(Victoria et al , 2016Lizasoain et al 2015;Tort et al 2015;Varela et al 2015;Lopez et al 2017). This information raises the need to evaluate the wastewater treatment process existing in the country to assure viral removal from wastewater and reach effluent of good quality.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, a wide dispersion as well as a wide genetic diversity in the Uruguayan environment has been recently reported for these viral pathogens (Victoria et al . , ; Lizasoain et al . ; Tort et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent environmental surveillance studies revealed that human noroviruses in the environment are sometimes more genetically diverse than are outbreak strains, suggesting that the genotype distribution of noroviruses associated with sporadic or asymptomatic infections is higher. In sewage samples, the proportion of GI versus GII noroviruses is often similar (30, 62), which could also indicate different survival characteristics for GI and GII viruses.…”
Section: Discussionmentioning
confidence: 99%